Anatomic Differences in Early Blindness: A Deformation‐Based Morphometry MRI Study. Issue 1 (13th January 2012) - Yang, Chunlan; Wu, Shuicai; Lu, Wangsheng; Bai, Yanping; Gao, Hongjian
ABSTRACT BACKGROUND AND PURPOSE This study aims to investigate the regional changes in the early onset of blindness using the deformation‐based morphometry (DBM) method. METHODS A total of 15 early blindness and 30 gender‐ and age‐matched sighted control subjects were recruited for the study. Statistically significant changes in regional volume were analyzed using DBM through HAMMER registration. Using this technique, changes in regional tissue volume can be detected on the basis of the deformation field derived from the warping subject to the template image. A voxelwise estimation of the morphological differences between the two groups can be acquired after applying a threshold (P < .001, uncorrected) to the statistic maps. RESULTS Regions with enlarged volume in the brains of blind subjects are mainly localized in the left associated visual cortex, posterior cingulated cortex, and cerebellum, whereas volume reductions are primarily localized in the left early visual cortex. CONCLUSIONS DBM is an effective method for detecting entire brain structural changes in blindness. Visual deprivation actually alters the local structural organization during the early critical periods of neurodevelopment. Volume increases outside the occipital lobe detected with DBM may suggest compensatory adaptations.